2013
DOI: 10.1515/crelle-2013-0104
|View full text |Cite
|
Sign up to set email alerts
|

Wonderful resolutions and categorical crepant resolutions of singularities

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Note however that if the categorical resolution is of "geometric origin", then all these notions coincide with the classical definition of crepancy. Namely, we have the proposition ( The existence of weakly crepant resolutions of singularities has been proved in a quite general context (see [2,3]). For instance, it is proved in [2] that all Gorenstein determinantal varieties (general, symmetric, skew-symmetric) admit weakly crepant resolution of singularities.…”
Section: Categorical Crepant Resolutions Of Singularitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Note however that if the categorical resolution is of "geometric origin", then all these notions coincide with the classical definition of crepancy. Namely, we have the proposition ( The existence of weakly crepant resolutions of singularities has been proved in a quite general context (see [2,3]). For instance, it is proved in [2] that all Gorenstein determinantal varieties (general, symmetric, skew-symmetric) admit weakly crepant resolution of singularities.…”
Section: Categorical Crepant Resolutions Of Singularitiesmentioning
confidence: 99%
“…Namely, we have the proposition ( The existence of weakly crepant resolutions of singularities has been proved in a quite general context (see [2,3]). For instance, it is proved in [2] that all Gorenstein determinantal varieties (general, symmetric, skew-symmetric) admit weakly crepant resolution of singularities. The existence of strongly crepant resolution seems to be a much more delicate issue.…”
Section: Categorical Crepant Resolutions Of Singularitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting question is to find new methods of construction of minimal categorical resolutions. An interesting development in this direction is the work [Ab12] in which a notion of a wonderful resolution of singularities (an analogue of wonderful compactifications) is introduced and it is shown that a wonderful resolution gives rise to a weakly crepant categorical resolution. This can be viewed as an advance on the first part of Proposition 3.7.…”
Section: Further Questionsmentioning
confidence: 99%
“…The construction of Λ also works when n is even but then Λ is not an NCCR, albeit very close to one. In particular one may show that D(Λ) is a "weakly crepant categorical resolution" of Perf(Y ), again in the sense of [12] (see [1] for an entirely different construction of such resolutions).…”
Section: Introductionmentioning
confidence: 99%